Subsequent Memory Effects in Schizophrenia - Collier, Azurii K. (Psychiatry Res, 2014)
Differential neural activation at encoding can predict which stimuli will be subsequently remembered or forgotten, and memory deficits are pronounced in schizophrenia. We used event-related fMRI to investigate subsequent memory effects for visual fractals in patients with schizophrenia (n=26) and healthy controls (n=28). Participants incidentally encoded the fractals during an oddball task and 10 minutes later they made old/new recognition memory judgments on 30 target fractals and 30 foil fractals. We found evidence for subsequent memory (SM, subsequently remembered > subsequently forgotten) effects on regional brain activation in both groups but with distinct patterns. Region of interest analyses in controls demonstrated SM activation in both medial temporal lobe (MTL) and fusiform cortex (FF), whereas patients showed SM effects only in the FF. There were no significant between group differences in MTL activation; however, patients demonstrated greater FF activation than controls. Notably, greater FF activation during successful encoding was associated with more severe negative symptoms. Exploratory whole brain analyses in patients demonstrated SM activation in the occipital pole, lateral occipital cortex, left inferior temporal gyrus, and fusiform cortex; whereas in controls there was no significant activation that survived correction for multiple comparisons. Our findings suggest that patients, particularly those with prominent negative symptoms, may activate FF as a compensatory strategy to promote successful encoding, with relatively less reliance on MTL recruitment.